Sensing and Control for Autonomous Vehicles Applications to Land, Water and Air Vehicles - Fossen, Thor I.; Pettersen, Kristin Y.; Nijmeijer, Henk.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This edited volume includes thoroughly collected on sensing and control for autonomous vehicles. Guidance, navigation and motion control systems for autonomous vehicles are increasingly important in land-based, marine and aerial operations. Autonomous underwater vehicles may be used for pipeline inspection, light intervention work, underwater survey and collection of oceanographic/biological data. Autonomous unmanned aerial systems can be used in a large number of applications such as inspection, monitoring, data collection, surveillance, etc. At present, vehicles operate with limited autonomy and a minimum of intelligence. There is a growing interest for cooperative and coordinated multi-vehicle systems, real-time re-planning, robust autonomous navigation systems and robust autonomous control of vehicles. Unmanned vehicles with high levels of autonomy may be used for safe and efficient collection of environmental data, for assimilation of climate and environmental models andto complement global satellite systems. The target audience primarily comprises research experts in the field of control theory, but the book may also be beneficial for graduate students. .
Vehicle Navigation Systems -- Localization and Mapping -- Path Planning -- Sensing and Tracking Systems -- Identification and Motion Control of Robotic Vehicles -- Coordinated and Cooperative Control of Multi-Vehicle Systems.
Keywords: Control engineering; Robotics; Automation; Mathematical optimization; Calculus of variations; Aerospace engineering; Astronautics; Computational intelligence; Control, Robotics, Automation; Control and Systems Theory; Calculus of Variations and Optimization; Aerospace Technology and Astronautics; Computational Intelligence